Transformable ECM Deprivation System Effectively Suppresses Renal Cell Carcinoma by Reversing Anoikis Resistance and Increasing Chemotherapy Sensitivity. Issue 43 (20th September 2022) - Wang, Lu; Li, Cong; Wang, Jiaqi; Yang, Guang; Lv, Yulin; Fu, Bo; Jian, Lingrui; Ma, Jinpeng; Yu, Jiaao; Yang, Zongzheng; Wu, Peng; Li, Guangbin; et al.
Abstract: Extracellular matrix (ECM) is crucial in various biological functions during tumor progression, including induction of anoikis resistance and cell adhesion‐mediated drug resistance (CAM‐DR). Fibronectin (FN) is a vital ECM component with direct regulatory effects on ECM‐mediated anoikis resistance and CAM‐DR, making it an attractive and innovative therapeutic target for depriving ECM in tumor tissue. Herein, an ECM deprivation system (EDS) is developed based on FN targeting self‐assembly peptide for constructing nanofibers in the ECM of renal cell carcinoma (RCC), which contributes to: i) targeting and recognizing FN to form nanofibers for long‐term retention in ECM, ii) reversing anoikis resistance via arresting the FN signaling pathway, and iii) serving as a drug‐loading platform for sensitizing chemotherapy by ameliorating CAM‐DR. The results reveal that EDS significantly reverses anoikis resistance of RCC cells by inhibiting the phosphorylation of FAK, a positive regulator of the FN signaling pathway. Meanwhile, EDS serves as a chemotherapy‐sensitizer of cancer, exerting significant synergistic effects with doxorubicin (DOX). In vivo validation experiments show that EDS effectively suppresses metastasis and tumor growth with chemotherapy resistance. Collectively, the innovative EDS notably inhibits the tumor‐promoting effect of ECM and may provide a novel approach for suppressing ECM and enhancing chemo‐drug sensitivity. Abstract : Transformable extracellular matrix (ECM) deprivation system (EDS) deprives the ECM of tumors and restraints cancer progression by targeting fibronectin (FN). The cage‐like nanofibers deprive the ECM of renal cell carcinoma (RCC) cells, which block the FN‐mediated tumor‐promoting signaling and ultimately reverse anoikis resistance and ameliorate cell adhesion‐mediated drug resistance (CAM‐DR).